Optimalisasi Sistem E-Kinerja dalam Manajemen Kinerja Pegawai di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Gianyar - Suardana, Ida Bagus Raka; Arimbawa, Made; Wisudawati, Ni Nyoman Sri; Pratiwi, Nuning Indah (Dinasti Research, 2026)
This study aims to analyze the implementation of the e-Performance system in managing employee performance, as well as to identify the driving and inhibiting factors and the efforts made to address implementation challenges at the Human Resources and Human Resource Development Agency of Gianyar Regency. The research adopts a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, involving informants selected purposively, including leaders and administrators responsible for the system. Data analysis applies the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation. The findings reveal that the implementation of the e-Performance system has not yet been fully optimal. Key challenges include limited digital competencies among civil servants, insufficient technical understanding in preparing and inputting Employee Performance Targets, low discipline in reporting performance activities, and technical issues within the system. To address these challenges, several measures have been undertaken, such as continuous technical guidance and training, the application of performance-based reward and punishment mechanisms, stricter enforcement of reporting discipline, and the appointment of a Person in Charge (PIC) to handle technical problems. These findings indicate that optimizing the e-Performance system requires not only technological readiness but also improved competencies, stronger policies, and a proactive work culture